2022
DOI: 10.1186/s12906-021-03498-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antidiarrheal activity of 80% methanol extract and solvent fractions of the leaf of Bersama abyssinica fresen (Melianthaceae) in mice

Abstract: Introduction The use of traditional medicinal plants in the management of diarrhea has long been practiced in Ethiopia. B. abyssinica fresen is one of the plants traditionally used to treat diarrhea whereas an in vivo study had not yet been conducted. Thus, this study aimed to evaluate the antidiarrheal activity of crude extract and solvent fractions of the leaf of B. abyssinica in mice. Methods Cold maceration within 80% methanol was used to extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
(45 reference statements)
0
13
1
Order By: Relevance
“…Additionally, the crude extract exhibited the highest ADI value across all the test treatments at the corresponding doses, showing that it might have higher antidiarrheal activity than the solvent fractions. Regarding viewing the antidiarrheal effect in consideration of the ADI value, the result of this study is not consistent with a result reported by Ayalew et al [ 45 ] which shows that the highest antidiarrheal activity might be produced by the chloroform fraction, whereas the highest activity was produced by the methanolic crude extract followed by the aqueous fraction in this study. The results are also differed from those of a study on the antidiarrheal effects of various solvent extracts of Tetrastigma leucostaphylum which reported that the percentage inhibition of diarrhea and antidiarrheal index values produced by the various organic solvents are generally greater than resulted by the methanolic extract [ 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, the crude extract exhibited the highest ADI value across all the test treatments at the corresponding doses, showing that it might have higher antidiarrheal activity than the solvent fractions. Regarding viewing the antidiarrheal effect in consideration of the ADI value, the result of this study is not consistent with a result reported by Ayalew et al [ 45 ] which shows that the highest antidiarrheal activity might be produced by the chloroform fraction, whereas the highest activity was produced by the methanolic crude extract followed by the aqueous fraction in this study. The results are also differed from those of a study on the antidiarrheal effects of various solvent extracts of Tetrastigma leucostaphylum which reported that the percentage inhibition of diarrhea and antidiarrheal index values produced by the various organic solvents are generally greater than resulted by the methanolic extract [ 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The crude extract and aqueous fraction at three doses ( p < 0.01 to p < 0.001), the chloroform fraction at 200 mg/kg and 400 mg/kg (p ˂ 0.01 to p ˂ 0.001), and the n-hexane fraction at 400 mg/kg (p ˂ 0.05) all reduced intraluminal fluid accumulation when compared to the negative control. The crude extract (70.83%) significantly suppressed Castor oil-induced intestinal motility by 70.83%, which is comparable to the positive control loperamide (75.0%) at 400 mg/kg ( Ayalew et al, 2022 ).…”
Section: Resultsmentioning
confidence: 59%
“…One of the mechanisms is that it produces the active metabolite ricinoleic acid by intestinal lipases. Ricinoleic acid stimulates the secretion of liquid and electrolytes and increases intestinal motility due to irritation and inflammation of the intestinal mucosa that leads to the release of prostaglandins [ 27 , 28 ]. Castor oil also inhibits intestinal Na + /K + -ATP-ase activity, which induces diarrhea by reducing normal fluid absorption [ 29 ].…”
Section: Discussionmentioning
confidence: 99%